Current Status of Bioprinting Using Polymer Hydrogels for the Production of Vascular Grafts - Jana Matějková; Denisa Kaňoková; Roman Matějka (Gels)
Cardiovascular disease is one of the leading causes of death and serious illness in Europe and worldwide. Conventional treatment—replacing the damaged blood vessel with an autologous graft—is not always affordable for the patient, so alternative approaches are being sought. One such approach is patient-specific tissue bioprinting, which allows for precise distribution of cells, material, and biochemical signals. With further developmental support, a functional replacement tissue or vessel can be created. This review provides an overview of the current state of bioprinting for vascular graft manufacturing and summarizes the hydrogels used as bioinks, the material of carriers, and the current methods of fabrication used, especially for vessels smaller than 6 mm, which are the most challenging for cardiovascular replacements. The fabrication methods are divided into several sections—self-supporting grafts based on simple 3D bioprinting and bioprinting of bioinks on scaffolds made of decellularized or nanofibrous material.